2011
DOI: 10.1111/j.1754-9485.2011.02281.x
|View full text |Cite
|
Sign up to set email alerts
|

Work engagement in cancer workers in Queensland: The flip side of burnout

Abstract: Approximately one-third of the workers sampled reported burnout. Conversely, one-third reported being highly engaged in their work. Further research is required to study the effectiveness of interventions to improve personal resources and prevent burnout. Understanding the factors associated with work engagement is equally important in designing organisational programs to enhance employee engagement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 13 publications
1
47
2
3
Order By: Relevance
“…Our finding that the UWES score did not differ significantly between trainees exceeding the EWTD limit and trainees who did not is in line with previous research, 9 but stands in contrast to those reported by other studies that have found that hours worked per week is positively associated with work engagement in registered nurses. 10 Again, job-related and study population characteristics may contribute to variations between study results.…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…Our finding that the UWES score did not differ significantly between trainees exceeding the EWTD limit and trainees who did not is in line with previous research, 9 but stands in contrast to those reported by other studies that have found that hours worked per week is positively associated with work engagement in registered nurses. 10 Again, job-related and study population characteristics may contribute to variations between study results.…”
Section: Resultscontrasting
confidence: 57%
“…8 Similarly, although in our study UWES scores did not differ significantly between married and unmarried participants, marital Table 1 Characteristics of the total sample of the study status has been associated with work engagement in cancer workers including nurses, radiation therapists, allied health, and medical staff. 9 These findings suggest that demographic characteristics may possibly play a different role in work engagement in diverse study populations and settings.…”
Section: Resultsmentioning
confidence: 83%
“…It is well recognised that this may contribute to burnout and the literature suggests that approximately one third of cancer workers exhibit symptoms of burnout, core features of which are emotional exhaustion and disengagement (Girgis et al, 2009;Poulsen et al, 2011;Shanafelt et al, 2006). Burnout and work stress are negatively correlated with employees' health and well being and are positively associated with high desire to leave the organisation (Coffeng et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…Self-efficacy in nurses will be low due to stressors. The stressors are high emotional demands in doing their work [12]. The stressors make the nurse burn out.…”
Section: Introductionmentioning
confidence: 99%